Phytochemical, Mineral, and Antioxidant Activity of Sugarcane Juice during Processing to Strawberry Syrup and Crystal Sugar - Rifqie Mariana Rina; Itorul Umam Nada; Gustiana Gunawan Aditia; dan Salsadela Salsadela (BIO Web of Conferences)
Indonesia is experiencing a significant increase in diabetes cases among teenagers, likely driven by the rising consumption of sugary drinks. These drinks often contain refined sugar, a known contributor to diabetes. Interestingly, sugarcane juice, the raw material for refined sugar, is rich in antioxidants, minerals, and Chromium III, which can enhance glucose absorption and reduce blood sugar levels. However, Chromium III is removed during the refining process. This study explores the potential of sugarcane juice combined with strawberries as a healthier alternative to refined sugar in beverages. The research analyzes the phytochemical composition, flavonoid, phenolic, antioxidant activity and selected mineral composition. The study shows strong antioxidant activity in sugarcane juice (28.8 ppm) and moderate activity in sugarcane syrup (58.1 ppm), with no antioxidant activity in white crystal sugar. Key component comparisons between sugarcane juice, syrup, and white sugar are as follows: chromium III (0.14, 0.09, 0), calcium (112.1 mg/L, 79.5 mg/L, 33.9 mg/L), potassium (918.1, 594.02 mg/L, 31.9 mg/L), flavonoids (12.47 mg QE/g, 5.75 mg QE/g, 0), and phenolic compounds (26.77 mg GAE/g, 5.86 mg GAE/g, 0). Hence, strawberry sugarcane syrup could be a promising health drink with potential benefits for lowering blood sugar levels in type 2 diabetes patients.